Management of hepatitis B virus infection, updated Swedish guidelines. Issue 1 (2nd January 2020) - Westin, Johan; Aleman, Soo; Castedal, Maria; Duberg, Ann-Sofi; Eilard, Anders; Fischler, Björn; Kampmann, Christian; Lindahl, Karin; Lindh, Magnus; Norkrans, Gunnar; Stenmark, Stephan; Weiland, Ola; et al.
Abstract: Despite access to effective antiviral drugs and vaccines, hepatitis B virus (HBV) infection remains a major health issue worldwide. HBV is highly infectious and may cause chronic infection, progressive liver damage, hepatocellular cancer (HCC) and death. Early diagnosis, proper management and timing of treatment are crucial. The Swedish Reference group for Antiviral Treatment (RAV) here provides updated evidence-based guidelines for treatment and management of HBV infection which may be applicable also in other countries. Tenofovir alafenamide (TAF) has been introduced as a novel treatment option and new principles regarding indication and duration of treatment and characterization of hepatitis B have been gradually introduced which justifies an update of the previous guidelines from 2007. Updated guidelines on HCC surveillance in HBV-infected patients, treatment and prophylaxis for patients undergoing liver transplantation as well as management of pregnant women and children with HBV infection are also provided.